“Sensitive and sustainable stability-indicating RP-HPLC method for simultaneous assay and impurity profiling of amitriptyline HCl: green metric, RGB model and forced degradation study" - Anand Radheshyam Tiwari; Sushama Raju Ambadekar; Vijay Arjun Bagul (Discover Chemistry)
Abstract A novel, sensitive, sustainable, and stability-indicating reverse-phase high-performance liquid chromatography method was developed to isolate and quantify amitriptyline hydrochloride and its impurities present in pharmaceuticals. The method employed an L1 column under isocratic elution conditions using a mobile phase comprising a phosphate buffer and acetonitrile, maintaining a flow rate of 1 mL/min. Detection of all analytes was performed using a photodiode array detector set at 215 nm. The method was validated as per International Council for Harmonisation guidelines for specificity, sensitivity, linearity, accuracy (limit of quantification–150%), precision, robustness, filter compatibility, and solution stability. The method showed excellent linearity for amitriptyline hydrochloride, with a quantitation range of 0.12–1.67 μg/mL for impurity determination and 255.49–766.48 μg/mL for assay linearity. Observed linearity ranges: nortriptyline (0.12–1.68 μg/mL), impurity-A (0.12–1.64 μg/mL), impurity-B (0.12–1.63 μg/mL), impurity-E (0.11–1.54 μg/mL). The method's stability-indicating properties were confirmed via stress tests (thermal, photolytic, acid–base, oxidative), with significant oxidative degradation observed. The method's environmental impact, efficiency, and sustainability were thoroughly assessed using recognized green metrics, including Analytical Eco-Scale, National Environmental Methods Index, Green Analytical Procedure Index, and Analytical Greenness, in alignment with Green Analytical Chemistry principles. Additionally, the red–green–blue color model based on White Analytical Chemistry was applied. The developed method is novel, sustainable, validated, and characterized by its short run time, simplicity, sensitivity, and stability-indicating properties. It enables simultaneous assay and impurity profiling, making it highly useful in research and development of new formulations and ensuring the quality and safety of pharmaceutical dosage forms throughout their shelf life. Graphical abstract